Alkaloid Constituents of Haplophyllum laeviusculum (Rutaceae). - Parhoodeh, Parimah; Rahmani, Mawardi; Mohd. Hashim, Najihah; Md.Sukari, Mohd. Aspollah; Ee, Gwendoline Cheng Lian (2012)
The investigation of the aerial parts of Haplophyllum laeviusculum (Rutaceae), a perennial herb native to Iran, afforded three alkaloids, skimmianine (1), lunamarine (2), ribalinidine (3) and and two common sterols, γ-sitosterol and campesterol. The structures of compounds were identified by using spectroscopic methods by using UV, IR, NMR, MS spectra and also by comparison with previous works. There has been no detail phytochemical investigation report on the plant carried previously. This is the first report on the identification of skimmianine (1), lunamarine (2) from genus Haplophyllum.